The Effect Of Thin Capitalization Towards Tax Avoidance Upon Finance Minister Regulation Pmk No. 169/Pmk.010/2015 On Healthcare Companies Listed In Idx From 2016 To 2021 - Sari, Prima (International Journal of Social Service and Research, 2024)
Government of Indonesia implemented thin capitalization rules to limit the debt shifting practice as a tax avoidance scheme after the regulation cancellation in 1985. The regulation had also been enforced since the 2016 Fiscal Year. This study examines the effect of thin capitalization toward tax avoidance upon PMK no.169/PMK.010/2015 on healthcare companies listed in IDX. Based on six healthcare companies listed in Indonesia Stock Exchange period 2016-2021, regression results indicate that the thin capitalization is significantly and positively influence with tax avoidance. Companies with high thin capitalization have thin effective tax rate. Meanwhile, firm size and profitability doesn’t have significant influence on tax avoidance.